APLIKASI MONITORING PEMELIHARAAN UNGGAS STUDI KASUS PADA ABDI POULTRY BERBASIS WEB - Wina Anjaningsih; Andreas Medi Marwanto; Dwi Ade Handayani Capah (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2021)
Poultry is a type of livestock group of birds that is used for meat and eggs or feathers. So far, Abdi Poultry is still recording the results of maintenance and poultry production manually, starting from recording the number of poultry seeds, recording sick or dead birds, recording feed, vitamins and drugs stocks, recording the number of poultry production. This manual recording makes documents prone to piling up and missing, difficulties in finding data, and inaccurate and detailed data. Based on the problems that occurred, an idea emerged to create a Web-Based Poultry Farm Monitoring Application that can support farmers' activities in data recording and monitoring which aims to simplify the poultry rearing process from seed to harvest. This application is made using the Waterfall system development method because this software development method allows system creation to be carried out in a structured and systematic (sequential) manner according to the development cycle that can provide solutions to existing problems.